Controversial effects of fumed silica on the curing and thermomechanical properties of epoxy composites (eXPRESS Polymer Letters)
The effect of fumed silica on the curing of a trimethylolpropane epoxy resin was investigated by thermal analysis methods like Differential Scanning Calorimetry (DSC), and Dynamic Mechanical Analysis (DMA). The fumed silica used here is a by-product of the silicon and ferrosilicon industry, consisting of micro and nanosized particles. Both the curing reaction and the properties of the obtained composites were affected by the filler content. Different trends were observed for filler contents above and below the 30 wt%. Up to 30 wt%, the behaviour can be explained as a predominantly agglomeration effect. For 30 wt% and higher filler contents, single particles seem to play a more important role.